Missed Testing Opportunities for HIV Screening and Early Diagnosis in an Urban Tertiary Care Center - Joseph DeRose; Jason Zucker; David Cennimo; Shobha Swaminathan (AIDS Research and Treatment)
Newark, New Jersey, is disproportionally affected by HIV with one of the highest prevalence rates in the United States. Rutgers New Jersey Medical School is a major healthcare provider to Newark’s underserved population and has implemented a HIV testing program that can diagnose and link newly diagnosed individuals to care. We conducted a retrospective chart review of all new patients seen in the Infectious Disease Practice from January 1, 2013, to December 31, 2014, to determine the proportion of patients with a missed testing opportunity (MTO) (patients with a new HIV diagnosis with an encounter at the institution in the 1 year prior to their first appointment). 117 newly diagnosed patients were identified. 36 (31%) had at least one MTO. A total of 34 (29%) of newly diagnosed patients had AIDS at presentation and 17% had CD4 counts of 50 cells/μL (p value 0.5). The two most common locations of a missed testing opportunity were the hospital ED (45%) and subspecialty clinics (37%). This study demonstrates that, even in a high prevalence institution with HIV counseling, testing, and referral service, HIV screening is lacking at multiple points of care and patients are missing opportunities for earlier diagnosis and treatment.